Laboratory experiments in physics for modern astronomy: with comprehensive development of the physical principles - Golden, Leslie M. (New York, Springer, 2013)
This book presents experiments which will teach physics relevant to astronomy. The astronomer, as instructor, frequently faces this need when his college or university has no astronomy department and any astronomy course is taught in the physics department. The physicist, as instructor, will find this intellectually appealing when faced with teaching an introductory astronomy course. From these experiments, the student will acquire important analytical tools, learn physics appropriate to astronomy, and experience instrument calibration and the direct gathering and analysis of data. Experiments that can be performed in one laboratory session as well as semester-long observation projects are included.
Appendix I-IV 551-559p.; Index 563-570p.
Keywords: Atomic spectra; Blackbody radiation; Orbit of venus; Formation of impact craters